Displacement of the Predominant Dengue Virus from Type 2 to Type 1 with a Subsequent Genotype Shift from IV to I in Surabaya, Indonesia 2008–2010 - Yamanaka, Atsushi; Mulyatno, Kris C.; Susilowati, Helen; Hendrianto, Eryk; Ginting, Amor P.; Sary, Dian D.; Rantam, Fedik A.; Soegijanto, Soegeng; Konishi, Eiji (PloS one, 2011)
Indonesia has annually experienced approximately 100,000 reported cases of dengue fever (DF) and dengue hemorrhagic fever (DHF) in recent years. However, epidemiological surveys of dengue viruses (DENVs) have been limited in this country. In Surabaya, the second largest city, a single report indicated that dengue virus type 2 (DENV2) was the predominant circulating virus in 2003-2005. We conducted three surveys in Surabaya during: (i) April 2007, (ii) June 2008 to April 2009, and (iii) September 2009 to December 2010. A total of 231 isolates were obtained from dengue patients and examined by PCR typing. We found that the predominant DENV shifted from type 2 to type 1 between October and November 2008. Another survey using wild-caught mosquitoes in April 2009 confirmed that dengue type 1 virus (DENV1) was the predominant type in Surabaya. Phylogenetic analyses of the nucleotide sequences of the complete envelope gene of DENV1 indicated that all 22 selected isolates in the second survey belonged to genotype IV and all 17 selected isolates in the third survey belonged to genotype I, indicating a genotype shift between April and September 2009. Furthermore, in December 2010, isolates were grouped into a new clade of DENV1 genotype I, suggesting clade shift between September and December 2010. According to statistics reported by the Surabaya Health Office, the proportion of DHF cases among the total number of dengue cases increased about three times after the type shift in 2008. In addition, the subsequent genotype shift in 2009 was associated with the increased number of total dengue cases. This indicates the need for continuous surveillance of circulating viruses to predict the risk of DHF and DF.